The Homiliary of Agimund and its implications for the availability of patristic texts in Rome in the early Middle Ages - McKitterick, Rosamond (The journal of ecclesiastical history, 2024)
Agimund's Homiliary is extant in two eighth-century manuscripts in BAV, Vat. lat. 3835 and 3836 and is one of the very few Roman texts actually written in Roman script surviving from the early Middle Ages. This article argues that the Homiliary is a crucial piece of evidence for early medieval Roman liturgical and cultural life and the patristic resources of Rome. Agimund's Homiliary, and the late eighth-century additions which are actually part of another, hitherto unidentified Roman Homiliary, together constitute evidence of the degree to which patristic theology and exegesis were embedded in Roman culture, of the interchange between the Latin- and Greek-speaking communities in Rome and the Lateran in the early Middle Ages, and of the intellectual productivity and cultural versatility of early medieval Rome.